A review on relationship of SNP at rs7975232 (ApaI) of VDR gene and different diseases in different population - Ahamed, Sharif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.